PRINSIP-PRINSIP NEGARA HUKUM INDONESIADALAM UUD NRI TAHUN 1945 - Putra Astomo (Program Studi Hukum Universitas Sulawesi Barat, 2018)
Human was thinking about law state developed in the various history situation of human culture. Although law state concept viewed as universal concept real have kind characteristic. The kind characteristic became principles which as must built. For example Indonesian State was law state mentioned in Article 1 Clause (3) Constitution 1945 years. After change Constitution 1945 years there are some principles Indonesian Law State include: law enforcement, Human Rights of protection, separation of power by check and balance system, limitation of power in the state, equality before the law, with Court Administration.